Effect of Mixture Strength and Injection Timing on Combustion Characteristics of a Direct Injection Hydrogen-Fueled Engine - Hamada, Khalaf I.; M. M., Rahman; M. A., Abdullah; R. A., Bakar; A. Rashid, A. Aziz (Elsevier, 2013)
An experimental investigation was performed to characterize the hydrogen combustion in a spark-ignition direct-injection engine. It was focused on the effects of mixture strength and injection timing on the characteristics of hydrogen combustion. For this purpose, the practical tests were carried out on an experimental test rig. It is originally designed for optimization of the direct-injection natural-gas engine. The experimental test-rig results comprised the traces for the in-cylinder pressure, mass fraction burned, and heat release rate under the different operation conditions. The results obtained show that the richer mixture condition produced higher pressure trends at all tested points. Besides that, it exhibited a faster rate of increase in combustion rate due to the increase of flame speed. However, the combustion characteristics deteriorated due to the lack of mixture stratification with earlier injection timing. It is concluded that direct-injection timing is essential to achieve better combustion performance. Moreover, retarding the spark ignition timing is also crucial to avoid abnormal combustion in the case of a richer mixture and early start on injection.